AB0272 Switching from Etanercept original to Etanercept biosimilar. EXPERIENCE IN A TERTIARY HOSPITAL. (2nd June 2020) - Aldasoro, V.; Mendizabal, J.; Perez Garcia, S.; Sada Urmeneta, G.; Restrepo Vélez, J.; Del Val del Amo, N.; Paniagua Zudaire, I.; Gutiérrez Polo, R.; Horcada, L.; Garrido Courel, L.; Fito-Manteca, C.
Abstract : Background: With the arrival of biosimilar drugs and savings policies to make the health system sustainable, hospital managers have chosen to make changes from original molecules to biosimilar drugs. Objectives: This work aims to reflect what happens when making these switchings. Methods: We reviewed 235 patients who started Etanercept original in Rheumatology at Navarra Hospital Complex and Henares University Hospital and their switch to Etanercept biosimilar with a follow-up of 6 months. Results: The switch was performed in 174 patients with psoriatic arthritis (PsA), rheumatoid arthritis (RA), ankylosing spondylitis (AS), juvenile idiopathic arthritis, SAPHO and spondyloarthritis. 9.8% discontinued treatment: 6 RA (8.1%), 5 PsA (9.8 %) and 6 AS (20.7%); all of them in the injection presentation. 12 patient stopped treatment due to ineffecacy, 2 due to reaction at the injection site, 2 due to diarrhea and 1 due to headache. Among 88.2% of patients who returned to Etanercept original, 28.6% did not achieve good response and had to change of treatment. The median time from Etanercept original beginning until the moment of switching was 54 (40-87) months. Conclusion: In our series, approximately 10% of switching patients failed after a 6-month of follow-up; when trying to return to Etanercept original 28.6% did not achieve response. The median persistence time in the original molecule and the percentage of failures observed in AS could be two conditions to consider before switching. A longer-term follow-up and a greater number of patients are necessary to ratify these data. Disclosure of Interests: Vicente Aldasoro Speakers bureau: Roche, Abbvie, MSD, UCB, Pfizer, Menarini, Grunenthal, Gebro, Novartis, Janssen, Javier Mendizabal: None declared, Sara Perez Garcia: None declared, Guillen Sada Urmeneta: None declared, Juliana Restrepo Vélez: None declared, Natividad del Val del Amo: None declared, Inmaculada Paniagua Zudaire: None declared, Ricardo Gutiérrez Polo: None declared, Loreto Horcada: None declared, Laura Garrido Courel: None declared, C. Fito-Manteca: None declared